2020
DOI: 10.1515/jpem-2020-0383
|View full text |Cite
|
Sign up to set email alerts
|

Papillary thyroid carcinoma in children with Hashimoto’s thyroiditis – a review of the literature between 2000 and 2020

Abstract: ObjectivesThyroid cancer is the most common pediatric endocrine neoplasm representing 3% of all malignancies in children. Hashimoto’s thyroiditis (HT) is also a common disorder in the pediatric age range. Patients with HT frequently develop enlarged thyroid with nodules. We aimed to provide a literature review on the frequency of papillary thyroid carcinoma (PTC) in patients with HT.ContentA literature search of the PubMed database between 2000 and 2020 was performed, using the relevant keywords “papillary thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 37 publications
0
10
0
3
Order By: Relevance
“…With regard to paediatric patients, the correlation between AIT and TC is still under discussion. Based on a review of reports published in the years 2000–2020, Sur et al concluded that the development of PTC in children with HT appeared to be higher than in the healthy population [ 38 ]. In Poland, a tenfold increase in the coexistence of AIT and TC was observed in children in the years 2001–2015 in comparison to the 15-year period before the year 2000 [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to paediatric patients, the correlation between AIT and TC is still under discussion. Based on a review of reports published in the years 2000–2020, Sur et al concluded that the development of PTC in children with HT appeared to be higher than in the healthy population [ 38 ]. In Poland, a tenfold increase in the coexistence of AIT and TC was observed in children in the years 2001–2015 in comparison to the 15-year period before the year 2000 [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…She did not have risk factors for thyroid malignancy; hence, a clinical diagnosis of thyroid malignancy was not entertained. Whilst Hashimoto's thyroiditis (HT) is the commonest risk factor associated with paediatric PTC [ 7 ], the patient did not report any history of autoimmune disease. Furthermore, histopathological assessment of thyroid did not reveal background HT.…”
Section: Discussionmentioning
confidence: 99%
“…[43], МФ разом з іншими ознаками пухлини є незалежним і важливим чинником, що визначає прогноз виживання пацієнтів з ДРЩЗ. При ПРЩЗ МФ пухлини є незалежним чинником ризику рецидиву [24,23,115], пов'язана з агресивнішим перебігом і гіршим прогнозом [41].…”
Section: таким чином попри високу роздільну здатність сучасних апарат...unclassified
“…У дитячому віці ТХ асоціюється з підвищеною частотою ПРЩЗ [115,135]. Однак при оцінці зв'язку між агресивністю ДРЩЗ у дітей з ТХ та без нього не виявлено статистично значущих відмінностей між групами як за частотою МФ, так і за демографічними даними, ЕТП, лімфоваскулярною інвазією, метастазами у ЛВ чи легені, рецидивом захворювання або РЙТ, але пацієнти з ТХ та ДРЩЗ частіше мали МФ, менші пухлини та мікрокальцифікати [133].…”
Section: більшість досліджень демонструють що ож призводить до агреси...unclassified
See 1 more Smart Citation